ANALISIS RASIO KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PADA PERUSAHAAN SEMEN DI BURSA EFEK INDONESIA - Khoidha, Rhesti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of research is to conduct whether the companies which are examined are the financial performance of cement companies in the IDX which are considered from liquidity ratio, the financial performance of cement companies in the IDX which is considered from solvability ratio, the financial performance of cement companies in the IDX which is considered from activity ratio, and the financial performance of cement companies in the IDX which is considered from profitability ratio. Descriptive qualitative approach is used by the researcher as the data analysis. It is performed by collecting, presenting and analyzing the data by using financial ratio analysis. Based result of inferential research concludes that when PT Indocement Tunggal Prakarsa Tbk is seen from the liquidity ratio and solvability ratio point of view, its liquidity ratio and solvability ratio are the best. When it is seen from the activity ratio and the profitability ratio point of view PT Semen Gresik is the best. Meanwhile, when it is seen comprehensively from all existing financial ratios, PT Semen Gresik Tbk is the best of the rest.Keywords: financial report analysis, financial ratio, cement company.